PWE-012 Audit Of Nhs Tayside Colonoscopy Surveillance Programme. (9th June 2014) - Elliott, K; Gray, L; Groome, M; Rodger, J; Mowat, C
Abstract : Introduction: Symptoms associated with organic bowel disease such as cancer or adenomatous polyps are extremely non-specific. 1 Therefore, for individuals at moderate and high risk of colorectal cancer (CRC), the current practice involves surveillance colonoscopy. 1 The BSG Guidelines for colorectal cancer screening and surveillance are a benchmark for UK clinicians. 1 Approximately 2500 patients are under regular endoscopic surveillance in NHS Tayside; appointments are booked following a review and telephone consult by nurse specialists. Methods: Aim: To determine the level of adherence to the BSG guidelines, and the pathology findings from recent colonoscopies. Methods: Patients on the surveillance register who were reviewed between September 2012 and June 2013 were studied. Electronic data was retrieved from Unisoft, ICE and Clinical Portal to view colonoscopy reports, pathology findings and follow-up plans. Results: 434 patients were reviewed. 319 requests adhered to the guidelines (adherence 73.5%), 328 patients (75.6%) were scoped: 27 declined, 1 moved out with Tayside, 1 referred to genetics, 31 weren't required, 10 were unfit, 33 weren't due for colonoscopy whilst 3 patients postponed. 44 patient's colonoscopies fell out with the guidelines; 2 weren't due, 4 weren't required, with the rest (38) being brought back too early/late. Median age 66 (range 21 – 96); Males 60%. Females 40%. Indication for surveillance was previous polyps (71%), carcinoma (11%), IBD (4%) or a genetic family history (14%). Colonoscopy identified normal bowel (58%), polyps (40%; 67% of these were adenomas), IBD (2%) and cancer (1%). Of 132 patients under 3 year follow-up for previous polyps; 54% had normal colonoscopy, 32% had adenomas. Of 60 patients under 5 year follow-up for previous polyps, 67% had normal colonoscopy, 18% had adenomas. Of 21 patients under 5 year follow-up for previous carcinoma 67% were normal, 19% had adenomas and there was one cancer. An additional 8 patients had a history of cancer within 3 years; 3 were found to have adenomas. Of 45 genetic family history patients 69% had normal colonoscopy, 18% adenomas. Out of 13 IBD patients 7 had normal colonoscopy, 2 active IBD and 4 polyps with 1 being an adenoma. Conclusion: In Tayside the adherence to BSG guidelines was 73.5%. The Nurse Specialist review saved a significant number of appointments. The majority of surveillance colonoscopies were normal; with the highest rate observed in those with a genetic family history. These findings suggest that alternative means of regular surveillance should be evaluated. Reference: Value of symptoms and additional diagnostic tests for colorectal cancer in primary care; systematic review and meta-analysis. BMJ 2010; 340:c1269doi:10.1136/bmj.c1269 Disclosure of Interest: None Declared.